Vanishing permanent glaciers : climate change is threatening a European Union habitat (Code 8340) and its poorly known biodiversity - Gobbi M.; Ambrosini R.; Casarotto C.; Diolaiuti G.; Ficetola G. F.; Lencioni V.; Seppi R.; Smiraglia C.; Tampucci D.; Valle B.; Caccianiga M. (Biodiversity and Conservation, 2021)
The cryosphere (i.e. glaciers and permafrost) and its related landforms offer a wide range of ecosystem services, thus they have strong relationships with human population. Even if these harsh environments have often been regarded as inhospitable, there is a growing amount of literature on glacial biodiversity, specifically concerning European mountains. Glaciers and permafrost-related landforms (e.g. rock glaciers) host a variety of cold-adapted taxa, from bacteria to vertebrates. They have been included in the Natura 2000 network, specifically in the habitat type: Permanent Glaciers (code 8340), but their biodiversity is still poorly known. Even if local extinctions and population reductions of cold-adapted species due to glacier and permafrost shrinking have been already documented, none of the species living in this habitat type are listed in the Habitat Directive Annexes. With this commentary, we call for urgent actions for an ecological characterization of this habitat type in order to plan monitoring and management of the biodiversity hosted by them. An increased knowledge of this no longer permanent habitat appears particularly urgent, because it is not replaceable and is likely to go extinct in the next decades.